The lion & the mouse - Pinkney, Jerry; Aesop (New York : Little, Brown and Co. Books for Young Readers, 2009)
In this wordless retelling of an Aesop fable, an adventuresome mouse proves that even small creatures are capable of great deeds when he rescues the King of the Jungle.
Caldecott 2009 Medal Winner
K-3
Keywords: Fables; Folklore; Fables; Folklore; Stories without words; Fables; Folklore; Stories without words; Picture books for children